Reflections on a Community Psychology Setting and the Future of the Field. Issue 3 (24th November 2016) - Kaufman, Joy S.; Connell, Christian M.; Crusto, Cindy A.; Gordon, Derrick M.; Sartor, Carolyn E.; Simon, Patricia; Strambler, Michael J.; Sullivan, Tami P.; Ward, Nadia L.; Weiss, Nicole Holland; Tebes, Jacob Kraemer
Abstract: The 50th anniversary of the Swampscott Conference offers an opportunity to reflect on a community psychology setting, The Consultation Center at Yale, that was formed in response to the 1963 Community Mental Health Act and the 1965 Swampscott Conference. The Center has flourished as a community psychology setting for practice, research, and training for 39 of the 50 years since Swampscott. Its creation and existence over this period offers an opportunity for reflection on the types of settings needed to sustain the field into the future.